Radon Concentrations and their Controlling Factors in Mud-built Houses in Dong Van Plateau Karst Geopark, Ha Giang Province - Duong, Nguyen Thuy; Nguyet, Nguyen Anh; Huong, Nguyen Van; Schimmelamann, Jan; Thai, Nguyen Dinh; Schimmelmann, Arndt (VNU Journal of Science: Earth and Environmental Sciences; Vol 36 No 1DO - 10.25073/2588-1094/vnuees.4547, 2020)
This article presents results of radon ( 222 Rn) and thoron ( 220 Rn) concentrations in room air measured inside mud-built houses that are traditional dwellings on the Dong Van Karst Plateau. The measurements were conducted in December 2016 and July 2017, corresponding to “cold” and “warm” months, respectively, by using a portable RAD7 detector. Our results show that 222 Rn and 220 Rn concentrations were elevated during the “warm” month and the concentrations of 220 Rn were always higher than the respective 222 Rn values at the same measured locations during the two months. The relatively long half-life of 222 Rn (3.83 days) causes efficient dispersion and loss from room air due to air ventilation. In contrast, the much shorter half-life of 220 Rn (55.6 seconds) results in elevated radiation near mud surfaces prior to attenuation into room air further away from walls and floors. Average concentrations of 220 Rn in room air during both “cold” and “warm” months are much higher than in normal outside air (~10 Bq m -3 ). The severely elevated concentrations of 220 Rn in room air of mud-built homes are likely harmful to human occupants, especially to those sleeping near mud-walls. Keywords: Radiation, radon gas, 222 Rn, 220 Rn, temperature, air ventilation.